Work Motivation Mediates: Relationship of Competence and Training on Auditor Performance - Suryono Efendi (Pusat Penerbitan dan Publikasi Ilmiah, FEB, Universitas Muslim Indonesia, 2022)
This study aims to examine and analyze the effect of competence, training and motivation on auditor performance. The effect of competence and training on work motivation. The effect of competence and training on auditor performance through mediation of work motivation. This research design uses an explanatory research approach with data collection carried out in one stage (one short study). The population in this study are auditors who work at a Public Accounting Firm (KAP) located in the South Jakarta area. The sampling technique was purposive sampling so that the total sample was 50 auditors. The data analysis technique in this study used Partial Least Square (PLS). The results of this study found that the competence possessed by the auditor can improve the performance of the auditor in carrying out his duties; audit training that is attended by the auditor is able to improve the performance of the auditor to complete the work in accordance with the standards set in a timely manner and can take advantage of the time. If the work motivation is getting better, it will have a direct effect on improving the performance of the auditor. Many or few competencies possessed by auditors do not affect their work motivation to complete audit tasks. High competence can make a significant contribution to increasing work motivation and auditor performance. If the training is getting better, it will have a direct effect on increasing motivation. The higher the training, the higher the employee's performance through increased motivation. This research can provide additional references to organizations/agencies, related to competence, training, and work motivation that affect the performance of auditors. It is expected that the auditor's performance can be in accordance with organizational goals. Organizations should maximize the increase and improve the quantity of their auditors' work. This study also provides a description of the effect of professionalism, independence, and auditor training on auditor performance which can be used as a reference for further research.